ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH PANDEMI COVID-19 PADA PT. MEDIA NUSANTARA CITRA, Tbk PERIODE 2018-2021 - Raden Roro Fara Diba; Eka Sudarmaji; M. Rubiul Yatim (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2023)
This study aimed to determine the differences in financial performance before and after the COVID-19 pandemic at PT. Media Nusantara Tbk for the 2018-2021 period. This study used quantitative research with financial ratios: Current Ratio, Debt to Equity Ratio, Return on Asset, Debt to Total Asset Ratio, and Total Asset Turnover. The data analysis method used was paired sample t-test. This study found that the current ratio after the Covid-19 pandemic is higher, with a larger average than before the Covid-19 pandemic. On the other hand, the Return on Assets before the Covid-19 pandemic was higher with a larger average than after the Covid-19 pandemic Total Asset Turnover was higher before the Covid-19 pandemic with a smaller average than after the Covid-19 pandemic. Moreover, the Debt to Equity was higher before the pandemic, and the Debt to Total Asset Ratio was higher with a smaller average than during the pandemic. In conclusion, there was no significant difference between the Current Ratio, Return on Asset, and Total Asset Turnover. However, there was a significant difference between the Debt to Total Asset Ratio and the Debt-to-Equity Ratio.